Coquerel [Athanase Josu] (Tufts Archival Research Center, 2008)
2.5 x 4.25. "Coquerel." Produced by: CH Reutlinger, Photographe, 21 Boulevart Montmartre, 21 et 112, Rue Richelieu, 112, Paris. These dates are approximate.